Enhancing caries-affected dentin bonding with a mussel-inspired primer - Hu, Yuntong; He, Yi; Wang, Dingjie; Wei, Yingjing; Xing, Xiaodong; Xiao, Yuhong (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionDental caries is the most common oral disease. In caries-affected dentin (CAD), excessive mineral loss, extensive collagen exposure and collapse, increased enzyme activity, and bacterial residues result in significantly lower resin bonding strength and durability compared to sound dentin (SD). Currently, there are no effective clinical strategies to enhance CAD bonding. Inspired by the excellent wet adhesion capability and collagen affinity of marine mussels, this study aimed to evaluate a mussel-inspired polymerizable monomer (catechol–Lys–methacrylate [CLM]) as a primer to improve CAD bonding performance.MethodsThe interactions between CLM and collagen were analyzed via Fourier-transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR). Microtensile bond strength, nanoleakage, in-situ zymography, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) were used to assess the bond strength and interface stability. Furthermore, the antibacterial properties of CLM were evaluated using colony-forming units counts, live/dead bacterial staining, and bacterial morphology observation.ResultsFTIR and NMR results showed that CLM was successfully grafted onto CAD collagen through its catechol groups, facilitating subsequent chemical bonding with resin. CLM increased the immediate CAD bond strength by approximately 30% and reduced immediate nanoleakage by approximately 24%, maintaining effectiveness after aging. Moreover, collagen chemical modification by CLM promoted collagen crosslinking, inhibited endogenous enzymatic activity, and conferred antibacterial properties, further enhancing bonding interface stability.DiscussionIn summary, this study reports the application of a mussel-inspired monomer, CLM, in CAD bonding. During the wet bonding process, CLM not only improves collagen stability but also serves as a molecular bridge between inorganic resin and organic collagen, thereby enhancing both immediate and aged bonding performance. These findings showing promising clinical application potential.